Association Between Cognitive Tests and Antiretroviral Medication Adherence in Older Adults With HIV. Issue 2 (February 2019) - Caballero, Joshua; Ownby, Raymond L.; Jacobs, Robin J.; Thomas, Jennifer E.; Schweizer, Mark S.
Background: One of the fastest growing populations living with HIV is older adults especially those 65 years of age or older. Current antiretroviral therapy (ART) has prolonged life expectancy of persons with HIV. However, for therapy to be effective, patients need to be adherent. Over time, older persons with HIV may experience HIV-associated neurocognitive disorders or other factors that could affect ART adherence. The use of expedient cognitive tests that help measure medication adherence may be useful for the optimal care of these patients.Objective: To investigate the association between cognitive tests and ART adherence.Methods: This was a prospective study evaluating patients 65 years of age or older with HIV. Cognitive tests used included the Executive Clock-Drawing Task (CLOX) 1 and 2, Trail Making Test parts A and B, and Grooved Pegboard Test (GPB). The medication event monitoring system cap over 1 month was used as the primary measure for adherence.Results: CLOX 1 and GPB were significantly related to adherence ( P < 0.05). Comparison of the magnitude of each measure's relation to adherence suggests that the GPB is a better indicator of ability to adhere ( R = 0.514 vs R = 0.381).Conclusion and Relevance: CLOX 1 and GPB demonstrated an association with adherence in patients 65 years of age or older with HIV. Although the use of these tests to measure adherence in older persons with HIV seems promising, more research is needed to ascertain their ultimate utility.